Standardized computer-based organized reporting of EEG: SCORE - Second version - Beniczky, Sándor; Aurlien, Harald; Brøgger, Jan C; Hirsch, Lawrence J; Schomer, Donald L; Trinka, Eugen; Pressler, Ronit M; Wennberg, Richard; Visser, Gerhard H; Eisermann, Monika; Diehl, Beate; Lesser, Ronald P; et al. (Clinical neurophysiology, 2017)
Standardized terminology for computer-based assessment and reporting of EEG has been previously developed in Europe. The International Federation of Clinical Neurophysiology established a taskforce in 2013 to develop this further, and to reach international consensus. This work resulted in the second, revised version of SCORE (Standardized Computer-based Organized Reporting of EEG), which is presented in this paper. The revised terminology was implemented in a software package (SCORE EEG), which was tested in clinical practice on 12,160 EEG recordings. Standardized terms implemented in SCORE are used to report the features of clinical relevance, extracted while assessing the EEGs. Selection of the terms is context sensitive: initial choices determine the subsequently presented sets of additional choices. This process automatically generates a report and feeds these features into a database. In the end, the diagnostic significance is scored, using a standardized list of terms. SCORE has specific modules for scoring seizures (including seizure semiology and ictal EEG patterns), neonatal recordings (including features specific for this age group), and for Critical Care EEG Terminology. SCORE is a useful clinical tool, with potential impact on clinical care, quality assurance, data-sharing, research and education.
Keywords: Clinical assessment; Database; software; Standardized; lidé; EEG; Terminology; Electroencephalography; Report; elektroencefalografie; Software; Brain; Humans; mozek